2000
DOI: 10.1088/0029-5515/40/8/305
|View full text |Cite
|
Sign up to set email alerts
|

Pellet fuelling into radiative improved confinement discharges in TEXTOR-94

Abstract: Normally pellet injection in strongly heated discharges leads at most to a relatively short improvement of the energy and particle confinement times. In contrast to this finding, the radiative improved (RI) mode plasma of TEXTOR-94 is a very well suited target for pellet injection: the interaction of a pellet with the high density plasma together with the radiatively cooled edge leads in the best cases to an improved energy confinement time which lasts to the end of the heating phase. The pellet injection caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The end of the enhanced confinement phase is triggered by the onset of a MARFE or by the increase in the neutral density at the edge in the case of multiple pellet injection. The most likely explanation is that the injected pellet does not create a new plasma mode of improved confinement but that it continues the RI mode to the upper limit, the density peaking allowing the stabilization of ITG modes deeper in the plasma core [213].…”
Section: Confinement and Transport Propertiesmentioning
confidence: 99%
“…The end of the enhanced confinement phase is triggered by the onset of a MARFE or by the increase in the neutral density at the edge in the case of multiple pellet injection. The most likely explanation is that the injected pellet does not create a new plasma mode of improved confinement but that it continues the RI mode to the upper limit, the density peaking allowing the stabilization of ITG modes deeper in the plasma core [213].…”
Section: Confinement and Transport Propertiesmentioning
confidence: 99%
“…The dependence of confinement quality on the heating method is another important issue (Messiaen et al 1997). Processes leading to the termination of the RI-mode through the development of large-scale MHD-instabilities (Koslowski et al 1999) or the formation of MARFEs triggered at the inner edge by pellet injection (Hobirk et al 1999) have to be considered. An analysis of RI-core plasmas combined with an H-mode barrier at the edge of large devices as JET provides a great challenge for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the effect of an ELM event on the radiation can give some valuable information about ELM mechanism. It was found that radiative cooling, which can give rise to improved confinement [13,14] or causes the formation of multifaceted asymmetric radiation from the edge (MARFE), [15] also plays an important role in triggering ELM events. The main impurities in the HL-2A are light impurities such as carbon and oxygen, and their profiles during H-mode, which are as long as profiles during L-mode, are shown in Fig.…”
Section: In Divertor Configurationmentioning
confidence: 99%